2012
DOI: 10.1109/tbme.2012.2190288
|View full text |Cite
|
Sign up to set email alerts
|

CNT/PDMS Composite Flexible Dry Electrodesfor Long-Term ECG Monitoring

Abstract: We fabricated a carbon nanotube (CNT)/ polydimethylsiloxane (PDMS) composite-based dry ECG electrode that can be readily connected to conventional ECG devices, and showed its long-term wearable monitoring capability and robustness to motion and sweat. While the dispersion of CNTs in PDMS is challenging, we optimized the process to disperse untreated CNTs within PDMS by mechanical force only. The electrical and mechanical characteristics of the CNT/PDMS electrode were tested according to the concentration of CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
91
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(95 citation statements)
references
References 29 publications
0
91
1
Order By: Relevance
“…The materials and fabrication processes are similar for contact and non-contact type electrodes, except that the electronics need to be adjusted for each. Some demonstrations include, carbon-nanotube or metal nanoparticle doped polymeric sensors [2][3][4], micromachined flexible sensors [5], minimally invasive needle type electrodes [6][7][8], and capacitive non-contact sensors based on printed-circuit board technologies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The materials and fabrication processes are similar for contact and non-contact type electrodes, except that the electronics need to be adjusted for each. Some demonstrations include, carbon-nanotube or metal nanoparticle doped polymeric sensors [2][3][4], micromachined flexible sensors [5], minimally invasive needle type electrodes [6][7][8], and capacitive non-contact sensors based on printed-circuit board technologies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Following the development of flexible and stretchable electronics, alternative electrodes that do not require electrolytic gel (referred to as active dry electrodes) have been reported by many groups [9,10,11,12,13,14,15,16]. Baek proposed flexible polymeric electrodes [9], and Lee developed a metallic material layer, carbon nanotube (CNT) and polydimethylsiloxane (PDMS) composite-based dry ECG electrode [10].…”
Section: Introductionmentioning
confidence: 99%
“…Baek proposed flexible polymeric electrodes [9], and Lee developed a metallic material layer, carbon nanotube (CNT) and polydimethylsiloxane (PDMS) composite-based dry ECG electrode [10]. Ruffini proposed a dry electrode based on multiwall CNT (MWCNTs) arrays to penetrate the patient’s outer skin cell layers and reduce the measurement noise [12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to interesting mechanical and electrical properties of carbon-based nanomaterials, carbon nanotubes (CNTs) are selected to disperse into the flexible polymer substrates to make a better conductive ECG electrode. Lee and his colleagues [11] fabricated a dry ECG electrode by dispersion of CNT into the PDMS layer to investigate the effects of CNT concentration and robustness to motion and sweat. Tests showed that there was no sign of signal degradation after continuously wearing the CNT/PDMS electrodes after exercise (in the presence of sweat), and for 7 days.…”
Section: Introductionmentioning
confidence: 99%